Aspetti demografici ed ideologici del populismo in Europa - Ruzza, Carlo; Loner, Enzo (SocietàMutamentoPolitica, 2017)
This article explores the socio-economic and attitudinal profile of voters of radical right populist in ten European countries. It provides confirmation of the so-called syndrome of the ‘losers of globalization’ which the literature indicates as a predictor of the radical right vote and which consists in perceptions of declining standard of living, blaming of migrants and generalized concerns with personal security. In addition, it examines the propensity to vote for radical right parties when they are, or are not, in an incumbent position. It hypothesizes that their electoral success will be inversely related to their incumbent role. This is because they are mainly defined and voted as anti-system parties, and any incumbent role undermines this self-characterization. The article provides confirmation of this hypothesis.